Risk Factors for Poor Outcome in Stroke - J Gordon Millichap (Pediatric Neurology Briefs)
Risk factors for stroke in children and their relationship to outcome were determined by reviewing charts of 72 patients with ischemic and hemorrhagic strokes at the Universities of Montreal and Toronto, Canada.